2017
DOI: 10.1515/gse-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Benthic Macroinvertebrates in Thi Vai River and Cai Mep Estuaries Under Polluted Conditions with Industrial Wastewater

Abstract: The pollution on the Thi Vai River has been spreading out rapidly over the two lasted decades caused by the wastewater from the industrial parks in the left bank of Thi Vai River and Cai Mep Estuaries. The evaluation of the benthic macroinvertebrate changes was very necessary to identify the consequences of the industrial wastewater on water quality and aquatic ecosystem of Thi Vai River and Cai Mep Estuaries.In this study, the variables of benthic macroinvertebrates and water quality were investigated in Thi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Similar to the species richness, the abundance of the invertebrates in the studied area was also quite low which could be due to the sandy bottom and the high water turbulence. These findings on dominant species that recorded in this study was quite similar to the previous results aquatic flora and fauna monitoring in the Can Gio Mangrove Biosphere Reserve [12,27,30] and the surrounding area as the coastal of Tien Giang Province [14,22]. However, the abundance of aquatic invertebrates was lower because of the sea waves and hard bottom beds in the coastal region.…”
Section: Abundance and Dominant Speciessupporting
confidence: 91%
See 4 more Smart Citations
“…Similar to the species richness, the abundance of the invertebrates in the studied area was also quite low which could be due to the sandy bottom and the high water turbulence. These findings on dominant species that recorded in this study was quite similar to the previous results aquatic flora and fauna monitoring in the Can Gio Mangrove Biosphere Reserve [12,27,30] and the surrounding area as the coastal of Tien Giang Province [14,22]. However, the abundance of aquatic invertebrates was lower because of the sea waves and hard bottom beds in the coastal region.…”
Section: Abundance and Dominant Speciessupporting
confidence: 91%
“…The polychaeta contributed highest species number in the benthic macroinvertebrates, 6 species gaining 33% of the total species number (Figure 3). These results were similar to the findings of aquatic invertebrate distribution at the Eastern Delta Coast at Daietta, Egypt [24] and the Thi Vai River, Vietnam [12]. Another study on macroinvertebrates in the mangrove forests in India indicated that the polychaetes contributed highest proportion in the organism assemblage [26].…”
Section: Species Richness Of the Invertebratessupporting
confidence: 88%
See 3 more Smart Citations